2021
DOI: 10.1177/02610183211009889
|View full text |Cite
|
Sign up to set email alerts
|

The politics of implementation: The role of traditional authorities in delivering social policies to poor people in Kenya

Abstract: The article contributes to understanding the political economy of implementation of social protection programmes at local level. Current debates are dominated by technocratic arguments, emphasizing the lack of financial resources, technology or skills as major barriers for effective implementation. Describing how chiefs, assistant-chiefs and community elders are routinely at the centre stage of core implementation processes, including targeting, enrolment, delivery, monitoring, awareness and information, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The findings discussed extensively in Rohregger et al (2021) showed that traditional authorities often play an important complementary role, where they take over functions of effective but inadequate formal institutions. They can also substitute or compete with ineffective formal institutions, for example, in the case of targeting scheme or bribery.…”
Section: Political-economy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The findings discussed extensively in Rohregger et al (2021) showed that traditional authorities often play an important complementary role, where they take over functions of effective but inadequate formal institutions. They can also substitute or compete with ineffective formal institutions, for example, in the case of targeting scheme or bribery.…”
Section: Political-economy Analysismentioning
confidence: 99%
“…Institutional accountability towards building voice and empowerment of vulnerable populations and emerging notions of social equity and sustainability were discussed in passing. The more in-depth analysis on regulatory frameworks and policy instruments, in the case of Kenya, was done in Bender et al (2021) and Rohregger et al (2021).…”
Section: Community Impacts Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation